Strategi Perencanaan Tenaga Kerja SDM UMKM Batik Ayu Telagasari - Yayat Febriyanti; Enjang Suherman; Flora Patricia Angela (Journal of Management and Bussines (JOMB), 2024)
This research aims to identify HR workforce planning strategies at Batik Ayu. The analysis was carried out using IFAS and EFAS analysis, followed by a SWOT matrix to find the position of the Labor quadrant. Batik Ayu faces the problem of not having an HR workforce planning strategy, which is the focus of this research. The research method used is a qualitative approach with the application of SWOT analysis. Data was obtained through interviews and surveys with MSME owners, employees and researchers as the main source of data. The results of the analysis show that Batik Ayu's workforce/HR is in quadrant 1 (positive), indicating access to various opportunities in the environment and the forces that support the use of these opportunities. The conclusion is that the recommended strategic plan is to implement growth policies with an aggressive approach to exploit these opportunities optimally. Keywords: SWOT Analysis, EFAS, IFAS Work, Energy